Voltage regulation of DC micro grid system using PV and battery coupled SEPIC converter - Rajaboyana Narendra Rao; Meda Sreenivasulu; Busharaju Ramakrishna (Institute of Advanced Engineering and Science, 2023)
This paper deals with the voltage regulation of DC micro grid system using photovoltaic and battery coupled single-ended primary-inductor converter (SEPIC) converter. SEPIC converter is a DC-to-DC boost converter, it can produce non pulsating DC current with less ripples when compared to buck and buck boost converters. Non pulsating DC current is the demanding condition required in maximum power point tracking (MPPT) applications and battery charging. This paper presents the simulation of the converters for both open and closed loop systems. Firstly, the proposed PV coupled SEPIC converter and the battery coupled buck boost converters are integrated to regulate the voltage in micro grid, and it is compared with the conventional methods in terms of output voltage, ripple voltage and power. The ripple voltage has been reduced to 0.1 V from 0.3 V in the proposed method. Secondly, PI and PID controllers are employed individually to SEPIC and buck boost converter for the voltage regulation of the DC micro grid system. The performance of the closed loop analysis is done in terms of time domain specifications, and it reveals that PID controller has the better response. The proposed system is simulated using MATLAB/Simulink and the prototype has been developed to verify the simulated results.